A COMPREHENSIVE ANALYSIS OF MARRIAGE AND INHERITANCE LAW IN THE LEGAL SYSTEM OF BRUNEI DARUSSALAM - Agus Gandara; Oyo Sunaryo; Aden Rosadi (SINERGI : Jurnal Riset Ilmiah, 2026)
This study analyzes the marriage and inheritance legal systems in Brunei Darussalam and compares them with those of Indonesia. Brunei, as an absolute monarchy guided by the Melayu Islam Beraja (MIB) ideology, comprehensively integrates Islamic Sharia into its national legal framework based on the Shafi'i school. Using a juridical-normative and comparative approach, this research finds that Brunei’s Islamic Family Law Act (Cap. 217) strictly regulates marriage, divorce, and post-divorce rights, including polygamy regulations that require the Sultan’s permission. In matters of inheritance, the faraidh system is implemented literally without significant modifications. Unlike Brunei, Indonesia—through the Compilation of Islamic Law (KHI)—has developed progressive innovations such as mandatory wills for adopted children and substitute heirs. These differences reflect the divergence between Brunei’s conservative-centralistic model and Indonesia’s progressive-pluralistic model, demonstrating that the implementation of Islamic law is largely determined by each country’s sociopolitical context